THE EFFECTIVENESS OF PROBLEM BASED LEARNING IN SOCIAL STUDY TOWARDS THE ENHANCEMENT OF LEARNING CREATIVITY OF STUDENTS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The purpose of this study is to find out, 1) how is the learning creativity of students in social studies lectures; 2) is there a difference in creativity in learning between learning based on problem based learning (PBL) and conventional learning in learning social studies; 3) is there the effectiveness of problem-based learning approaches (PBL) in learning social studies on student learning creativity. This study is a quasi experimental research, with pretest-postes design using a control group without random assignment. The sample of the pilot study is a 16 th grade A-class student of PGSD FKIP SWCU FKIP with 24 students and 16 E class with 24 students. Technique of collecting data by using test and direct observation. The research instrument test items and observation sheets are equipped with an assessment rubric The research instrument used an observation guide with a measurement rubric. Technique of data analysis using t-test with significance level ? = 0,05 that is to analyze difference of mean score of independent sample t-test creativity score of control group and experiment group and aid program SPPS version 23,0. The results showed that: 1) The importance of creativity in learning is that students are directly involved in learning, creative students are able to solve problems and have the potential to produce works; 2) Implementation of Social Study learning with PBL approach through step a). Formulate the problem, b). Review social studies learning, c). Formulate social studies learning hypotheses and learning outcomes, d). Gather information, e). Troubleshooting and solutions, and f). Presentation. Creative learning lattice: a). the magnitude of the score for the formulation of social studies learning problems, b). the magnitude of the score from the study of social studies learning, c). the magnitude of the score for the formulation of the Social Studies learning hypothesis and the learning outcomes, d). the amount of score in solving problems and solutions, and e). the magnitude of the score during the presentation, 3) there is effectiveness of PBL approach to student's learning creativity. This can be seen from the significant value of the same variance assumed (2-tailed) learning creativity of Social Study <0.05. According to the basis of decision making in independent t-sample test, it can be concluded that Ho is rejected and Ha accepted, meaning that there is difference of mean value of learning creativity between experiment group and control group. Result of t test is bigger than t table, it means Ho is rejected and Ha accepted.